Effect of capmatinib on the pharmacokinetics of substrates of CYP3A (midazolam) and CYP1A2 (caffeine) in patients with MET‐dysregulated solid tumours. Issue 3 (17th October 2022) - Chen, Xinhui; Isambert, Nicolas; López‐López, Rafael; Giovannini, Monica; Pognan, Nathalie; Kapoor, Shruti; Quinlan, Michelle; You, Benoit; Cui, Xiaoming; Rahmanzadeh, Gholamreza; Mau‐Sorensen, Morten
Abstract : Background: Preclinical studies showed that capmatinib reversibly inhibits cytochrome P450 (CYP) 3A4 and CYP1A2 in a time‐dependent manner. In this study, we evaluated the effect of capmatinib on the exposure of sensitive substrates of CYP3A (midazolam) and CYP1A2 (caffeine) in patients with mesenchymal–epithelial transition ( MET )‐dysregulated solid tumours. Besides pharmacokinetics, we assessed treatment response and safety. Methods: This open‐label, multicentre, single‐sequence study consisted of a molecular prescreening period, a screening/baseline period of ≤28 days and a drug‐drug interaction (DDI) phase of 12 days. On day 1 of the DDI phase, 37 patients received a single oral dose of midazolam 2.5 mg and caffeine 100 mg as a two‐drug cocktail. Capmatinib 400 mg bid was administered from day 4 on a continuous dosing schedule. On day 9 of the DDI phase, patients were re‐exposed to midazolam and caffeine. After the DDI phase, patients received capmatinib on continuous 21‐day cycles until disease progression at the discretion of the investigator. Results: A 22% (90% confidence interval [CI] 7‐38%) increase in the midazolam maximum plasma concentration ( C max ) was noted when administered with capmatinib, but this was deemed not clinically meaningful. Co‐administration with capmatinib resulted in 134% (90% CI 108‐163%) and 122% (90% CI 95‐153%) increases in the caffeine area under the plasma concentration‐time curve from time zero to infinity (AUCinf ) and area under the plasma concentration‐time curve from time zero to the last measurable point (AUClast ), respectively, with no change in C max . Adverse events were consistent with the known capmatinib safety profile. No new safety signals were reported in this study. Conclusion: The data from this study demonstrated that capmatinib is a moderate CYP1A2 inhibitor. Capmatinib administration did not cause any clinically relevant changes in midazolam exposure.